Biotransformation of lignan glycoside to its aglycone by Woodfordia fruticosa flowers: quantification of compounds using a validated HPTLC method - Shikha Mishra; Vidhu Aeri (Taylor & Francis Group, 2017)
Context: Saraca asoca Linn. (Caesalpiniaceae) is an important traditional remedy for gynaecological disorders and it contains lyoniside, an aryl tetralin lignan glycoside. The aglycone of lyoniside, lyoniresinol possesses structural similarity to enterolignan precursors which are established phytoestrogens. Objectives: This work illustrates biotransformation of lyoniside to lyoniresinol using Woodfordia fruticosa Kurz. (Lythraceae) flowers and simultaneous quantification of lyoniside and lyoniresinol using a validated HPTLC method. Materials and methods: The aqueous extract prepared from S. asoca bark was fermented using W. fruticosa flowers. The substrate and fermented product both were simultaneously analyzed using solvent system:toluene:ethyl acetate:formic acid (4:3:0.4) at 254 nm. The method was validated for specificity, accuracy, precision, linearity, sensitivity and robustness as per ICH guidelines. Results: The substrate showed the presence of lyoniside, however, it decreased as the fermentation proceeded. On 3rd day, lyoniresinol starts appearing in the medium. In 8 days duration most of the lyoniside converted to lyoniresinol. The developed method was specific for lyoniside and lyoniresinol. Lyoniside and lyoniresinol showed linearity in the range of 250-3000 and 500-2500 ng. The method was accurate as resulted in 99.84% and 99.83% recovery, respectively, for lyoniside and lyoniresinol. Conclusion: Aryl tetralin lignan glycoside, lyoniside was successfully transformed into lyoniresinol using W. fruticosa flowers and their contents were simultaneously analyzed using developed validated HPTLC method.